Indigenous cellulosic Raw Materials for the Production of Pulp, Paper and Board Part XXIII.-chemical Pulps and Writing and Printing Papers from SAccharum procerum Roxb. (Bhutang) - Brat, R. V.; Jaspal, Nahendra S. (Indian Forester, 1954)
Laboratory experiments on the sulphate pulping of Saccharum procerum Roxb. ( bhutang ) are described. Two pilot plant trials were carried out. The average fibre length of the pulp from bhutang is 2.30 mm. Easy bleaching pulps in yields considerably higher than usually obtained from bamboo or sabai grass were obtained. Writing and printing papers made on the pilot plant were characterized by good formation and satisfactory strength properties. Two samples of papers made from bhutang are appended in this bulletin.